Litter Nutrient Dynamics in Quercus semecarpifolia Sm. Forests of Western Himalaya - Panwar, Vijender Pal (Indian Forester, 2022)
Litterfall plays an important role in carbon and nutrient cycling of a forest ecosystem influenced by climate, vegetation, forest type and age. The study evaluate the litter production and estimate the amount of nutrient returned through it to the forest floor of Quercus semecarpifolia. The species commonly occur at an altitude of 2400-3600 m AMSL in the western Himalayas. Maximum annual litter production was recorded 8474.15 kg ha-1yr-1. On average, 7386.35 kg ha-1 yr-1of leaf litter was recorded, which contributed about 87 percent to the total litter production. Minimum contribution (36.65 kg ha-1 yr-1) was through bark litter. Analysis of monthly data showed maximum litterfall during May (2510.50 kg ha-1) and minimum during October (384.15 kg ha-1). Nutrient content in the litter showed a reverse trend that higher nitrogen content was recorded during August (1.548) and minimum during May (1.074). Maximum contribution to nitrogen concentration was observed through leaf litter and minimum through the reproductive litter. Phosphorous concentration was also recorded with a maximum from August to October and a minimum during May and July. Overall, the nutrient return showed the annual pattern in the order of Ca > N > K > Mg > P.Â 